2021
DOI: 10.3390/brainsci11121561
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Hippocampal Astroglial Activity by Synaptamide in Rats with Neuropathic Pain

Abstract: The present study demonstrates that synaptamide (N-docosahexaenoylethanolamine), an endogenous metabolite of docosahexaenoic acid, when administered subcutaneously (4 mg/kg/day, 14 days), exhibits analgesic activity and promotes cognitive recovery in the rat sciatic nerve chronic constriction injury (CCI) model. We analyzed the dynamics of GFAP-positive astroglia and S100β-positive astroglia activity, the expression of nerve growth factor (NGF), and two subunits of the NMDA receptor (NMDAR1 and NMDAR2A) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…We have previously discovered that synaptamide treatment after the chronic constriction injury of the sciatic nerve affects the neuropathic pain development in rats, resulting in significantly less pronounced pain-like behavior [ 24 , 25 , 26 ], including a decrease in cold allodynia [ 25 , 26 ], as well as thermal [ 24 ] and mechanical hyperalgesia [ 26 ]. Furthermore, daily synaptamide administration prevents increased anxiety, and the impairment of locomotor activity, working, and long-term memory, caused by neuropathic pain syndrome [ 24 , 25 ]. Synaptamide administration for 35 days after sciatic nerve injury reduces inflammation in the lumbar spinal cord [ 26 ] and the hippocampus [ 24 ] by decreasing microglia activity and proinflammatory cytokine concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously discovered that synaptamide treatment after the chronic constriction injury of the sciatic nerve affects the neuropathic pain development in rats, resulting in significantly less pronounced pain-like behavior [ 24 , 25 , 26 ], including a decrease in cold allodynia [ 25 , 26 ], as well as thermal [ 24 ] and mechanical hyperalgesia [ 26 ]. Furthermore, daily synaptamide administration prevents increased anxiety, and the impairment of locomotor activity, working, and long-term memory, caused by neuropathic pain syndrome [ 24 , 25 ]. Synaptamide administration for 35 days after sciatic nerve injury reduces inflammation in the lumbar spinal cord [ 26 ] and the hippocampus [ 24 ] by decreasing microglia activity and proinflammatory cytokine concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Synaptamide administration for 35 days after sciatic nerve injury reduces inflammation in the lumbar spinal cord [ 26 ] and the hippocampus [ 24 ] by decreasing microglia activity and proinflammatory cytokine concentrations. Synaptamide also improves neurogenesis in the dentate gyrus subgranular zone of the hippocampus 14- and 35-days post-injury [ 24 , 25 ]. as well as stabilizes astroglial activity and increases the expression of nerve growth factor (NGF) and two subunits of N-methyl-D-aspartate (NMDA) receptors in the hippocampus 14 days after nerve trauma [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 32 Cognitive and emotional-behavioral impairments caused by the onset of neuropathic pain are associated with hippocampal neurogenic deficits. 34 Neuropathic pain has also been reported to inhibit differentiation into mature neurons in the hippocampal dentate gyrus region in parallel with reduced survival of neoplastic cells. 17 It has been reported that exercise works to prevent the onset of pain and eliminate pain after injury, and 58/64 (90%) articles published on the topic of exercise-induced analgesia showed a positive effect of exercise with only one activity.…”
Section: Discussionmentioning
confidence: 99%